Fourier Transform Infrared Spectral Analysis of Agars of Gelidium micropterum and Gracilaria fergusonii - RAJASULOCHANA, N.; GUNASEKARAN, S. (Asian Journal of Chemistry, 2010)
The present work aims to make an analysis of the samples of agars obtained from Gelidium micropterum and Gracilaria fergusonii collected at summer and winter seasons by FTIR spectroscopic method. The qualitative analysis on the vibrational bands has been carried out. Further the spectra have been compared with that of Difco agar.